Temperature sensing based on ethanol-filled photonic crystal fiber modal interferometer - Qian, Wenwen (2013)
A modal interferometer made of a short ethanol-filled photonic crystal fiber (PCF) combined with a fully collapsed splicing with single-mode fibers (SMFs) is proposed for temperature measurement. Two fully collapsed splicing regions between the ethanol-filled PCF and SMFs excite and recombine two interfering modes in the ethanol-filled PCF. The interference spectrum of the ethanol-filled PCF is more sensitive to temperature than that of original PCF. By monitoring one peak wavelength shift of the ethanol-filled PCF modal interference spectrum, the temperature sensitivity reaches up to -0.35 nm/°C for a 3.25-cm long ethanol-filled PCF.